Educational interventions used to improve the cognitive and social development of children and adolescents with autism (Research, Society and Development, 2021)
Difficulty in communication and socialization are the main characteristics presented by individuals diagnosed with autism. For children and adolescents with autism to have a better inclusion and understanding of the contents covered in the classroom, several methodologies have been developed and used that include active ASD teaching and learning strategies. Therefore, this study aimed to carry out a systematic review to verify which educational interventions have been used to improve the cognitive and social development of children and adolescents diagnosed with autism. For this reason, a search for scientific articles published between the years 2015 and 2020 was carried out in the Scielo, PubMed, Lilacs, Bireme, and Medline databases. The research included only studies that aimed at social and educational interventions for children and adolescents (2 to 18 years old) with autism. In the bibliographic survey, 227 articles were found. From the application of inclusion and exclusion criteria, 16 articles were evaluated in this systematic review. The studies addressed educational strategies that explored various aspects related to vision, hearing, smell, language, and sociability. The use of technological resources (applications, virtual games, video modeling, and robots) stimulated the cognitive and social development of the evaluated population. The results presented were favorable for the increase, mainly, in the frequency of non-verbal initiatives and the use of eye contact in responses to communication partners.